Navigating a trilemma: Energy security, equity, and sustainability in the Philippines' low-carbon transition. (January 2018) - La Viña, Antonio GM; Tan, Joyce Melcar; Guanzon, Teresa Ira Maris; Caleda, Mary Jean; Ang, Lawrence
Abstract: Nearly a decade after the Philippines began promoting renewable energy through legislation, the country has seen gains and encountered roadblocks in its transition to low carbon. This paper examines the Philippines' experience in attempting to escape conditions of lock-in and path dependency on fossil fuels, and attempting a governed transition to low-carbon energy sources. The Philippines is a developing country with substantial economic growth aspirations, yet it is among the most vulnerable to climate change, so it has great interest in mitigating global carbon emissions. Yet, the country itself is heavily dependent on imported coal for its energy needs. In the context of its existing regulatory and techno-institutional landscape, the authors examine the Philippine experience in governing its energy transition. The paper discusses challenges in balancing the trilemma of energy security, equity, and sustainability. It then identifies some priorities for the Philippines as it attempts to move away from fossil fuel dependency and accelerate its transition towards low-carbon energy. The authors consider developments beyond the energy sector, particularly the early entry-into-force of the Paris Agreement, as a tool to favor the trilemma's sustainability pillar. The Philippine case may provide lessons for other developing countries undergoing their own transitions.